(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
In tropical regions, postpartum anestrus is one of the main causes that limit production and reproductive efficiency of the double purpose cattle raising where the calf is used as somatosensory support for milk production. The continuous breastfeeding and the constant presence of the calf inhibit the secretion of GnRH in the hypothalamus due to increased endogenous opioids and estradiol in the hypothalamus and pituitary, negatively affecting the specificity of GnRH. The restricted breastfeeding is used as a management option to reduce the negative suck originated effects of the calf on postpartum ovarian activity. Different models of restricted feeding (early weaning, weaning time, feeding once per day, canned) used in double purpose cattle rising is different in technique and procedure, often obtain different results.